Meta-analysis on the safety and efficacy of long-term garlic consumption as an adjunctive treatment for hypertension - Tang, Yiyue; Lei, Yunzhen; Xu, Ming; Tu, Qingxian; Mao, Xiaochun; Huang, Nanqu; Jiang, Qianfeng (Frontiers in Nutrition, 2025)
ObjectivesThis systematic review and meta-analysis aimed to synthesize existing evidence, quantify the overall effect of garlic intervention on blood pressure, and explore potential variations in its effects under different population, formulation, and intervention duration conditions. This provides scientific evidence to support the clinical application of garlic in non-pharmacological interventions for hypertension.MethodsThis systematic review and meta-analysis strictly adhered to the protocol registered with PROSPERO (CRD420251055848) and followed the guidelines outlined in the PRISMA statement. We conducted a comprehensive search of PubMed, Web of Science, Embase, and the Cochrane Library from their inception to May 10, 2025. Inclusion criteria were based on the PICOS framework: patients with a clear diagnosis of hypertension, treated with garlic or garlic products, compared with conventional medications or a placebo, with clearly defined outcome measures, and randomized controlled trials (RCTs). Meta-analysis was performed using Stata 14.0 software, assessing heterogeneity using the Q-test and I2 statistic, and publication bias using Egger’s test.ResultsA total of 1,877 articles were retrieved, with 10 RCTs ultimately included in the meta-analysis. The results indicated a significant reduction in systolic blood pressure (SBP) (effect size: −4.21, 95% CI: −5.74 to −2.69, P < 0.001) and diastolic blood pressure (DBP) (effect size: −3.13, 95% CI: −4.42 to −1.84, P < 0.001) in the garlic intervention group compared to the control group. High-density lipoprotein (HDL) significantly increased (effect size: 0.31, 95% CI: 0.03 to 0.59, P = 0.03), and tumor necrosis factor-α (TNF-α) significantly decreased (effect size: −0.38, 95% CI: −0.72 to −0.04, P = 0.03). Subgroup analyses for SBP indicated significant reductions with a garlic dosage of 2.4 mg, an 8-weeks intervention, and in populations aged 50–60 years, with BMI of 18.5–24.9 and 30.0–34.9, baseline SBP of 130–139 mmHg and 140–149 mmHg, and baseline DBP of 70–79 mmHg and 90–100 mmHg. The incidence of adverse reactions in the garlic group was slightly higher, but not statistically significant, with gastrointestinal discomfort and bad breath being the most common side effects. Meta-regression analysis revealed that intervention duration, patient age, family history of cardiovascular disease, baseline SBP, and baseline DBP were positively correlated with the antihypertensive effect. S-allylcysteine (SAC) was negatively correlated, with an optimal dosage range of 0.5–1.5 mg.ConclusionThis meta-analysis suggests that garlic intervention has a significant effect on reducing blood pressure in certain populations, including those who are obese, aged 50–60, or have higher DBP. However, the overall impact on hypertension may be limited. Potential gastrointestinal and other adverse effects should be considered in clinical practice.